PATHOGENIC AND CORRELATIVE RELATIONSHIP BETWEEN THE LEVEL OF SHORT- CHAIN FATTY ACIDS AND THE INTENSITY OF BIOLOGICAL PROCESS IN CERVICAL CANCER CELLS DURING CANCEROGENESIS - E. V. Kayukova; T. E. Belokrinitskaya; T. V. Kayukova; B. S. Khyshiktuev (Сибирский онкологический журнал, 2018)
Background. The change in the spectrum of short-chain fatty acids (SCFA) is known to be one of the links of carcinogenesis.The aim of study was to assess the correlation between the levels of cell proliferation, apoptosis, cell cycle kinetics and the spectrum of short-chain fatty acids in cervical dysplasia and cancer cells.Methods. To analyze the association between the variables, the Spearman’s rank correlation was used.Results. The SCFA is likely to have anti-proliferative, pro-apoptotic, and modulatory effects on the cell cycle phase.Conclusion. Correlations between the level of SCFA and parameters of apoptosis, necrosis, and cell cycle phases indicates their pathogenetic participation in the cervical carcinogenesis.